Bukit Kepok Enterprise : "X3-Pro Sprayer" / Zainal Abidin Norhazam...[et.al] - Norhazam, Zainal Abidin; Ismail, Siti Aminah; Md Razali, Mohd Nor Fikri; Sihi@Ab Manaf, Zazmir; Sallehudin, Muhammad Safuan (Faculty of Plantation and Agrotechnology, 2017)
Agriculture is important to human being because plant is primary sources for people to eat. In Malaysia, agriculture sector is second largest contribution in Malaysia's economy. So, government fully support farmers who want to start their business in agriculture sector.